Leadership and work motivation from the cross cultural perspective - Mohd. Israil, Khaliq Ahmad (2010)
The purpose of this paper is to compare and contrast conventional management thought, its main features of leadership, and work motivation with those from an Islamic perspective. The paper fills in the literature gap that exists, despite the growing importance of a need for knowledge on management from an Islamic perspective. This paper is conceptual in nature. Therefore, the method adopted is descriptive and approached using revealed knowledge sources, as well as knowledge from conventional management literature from the cultural school of management thought. Leadership and motivational concepts in Islamic management are more comprehensive than the conventional theories. Islamic motivation frameworks also provide fundamentals for developing a strong Islamic leadership. Implications of these Islamic management concepts are not only confined to this materialistic world but also have connotation for subscribers of the belief of attaining eternal success in the hereafter. The paper gives a better understanding and guidelines for managers of multinational corporations, especially those working in Muslim countries, in order to achieve their corporate objectives successfully.